The Influence Of Brand Experience On Customer Loyalty Mediated By Customer Satisfaction PT Kereta Api Indonesia (Persero) Daop 2 Bandung On The Baturraden Express Train Executive Class - Shafa Silma Alifah; Kiagus Muhammad Amran; Nur Aziz Sugiharto (Institut Pendidikan Alfatah Mataram, 2026)
PT Kereta Api Indonesia (Persero) DAOP 2 Bandung uses occupancy data as the main evaluation tool to optimize service strategies. The research focused on the Baturraden Express Train to understand the relationship between brand experience, customer satisfaction, and customer loyalty, to improve service and customer satisfaction for the company's long-term success. In this research, the research method used is descriptive and verification with a quantitative approach. Descriptive research aims to provide a structural and factual explanation of the relationship between the variables studied, while verification is used to test hypotheses. Descriptive research will answer the previous questions regarding Baturraden Express Train passengers' views on brand experience, customer loyalty, and customer satisfaction. Meanwhile, verification will test the relationship between brand experience and customer loyalty, which is mediated by customer satisfaction. The survey method is used to collect data from phenomena that occur factually. The sampling method in this research used non-probability sampling with a purposive sampling technique with a total of 340 respondents. Quantitative methods based on positivism were used to test hypotheses with research instruments and statistical analysis. The data analysis technique was carried out using the Structural Equation Model (SEM) method, with data processing assisted by SEM-SmartPLS software. With the expected results, Brand Experience, Customer Loyalty, and Customer Satisfaction will have a positive and significant influence